Tinjauan Hukum Bisnis atas Tanggung Jawab Pelaku Usaha Ta’aruf Online terhadap Kasus Cyberbullying di Facebook (International Forum of Researchers and Lecturers, 2025)
Paid online matchmaking services that have developed through Facebook use consumer profiles to promote and find partners. This practice raises legal issues, particularly those related to consumer protection and the risk of digital harassment—also known as cyberbullying—in the form of derogatory, discriminatory, or offensive comments about consumers' personal standards that are displayed publicly. The purpose of this study is to assess the legal liability of business actors for cyberbullying when operating online matchmaking services and to assess the extent to which legal protection tools are available to consumers. This study uses a normative legal approach, utilizing case studies of legislation and conceptual studies on the practice of paid matchmaking services on social media. The results of the study show that businesses are required to guarantee the safety, comfort, and protection of consumer rights in all digital-based commercial activities, including managing content and interacting with people on social media. Non-material losses, such as psychological pressure and abuse of consumer dignity, are caused by a lack of supervision and a lack of moderate comment mechanisms. Therefore, regulations on personal data protection must be strengthened, content moderation responsibilities must be determined, and legal accountability mechanisms for business actors in the digital ta'aruf business must be made clear.